A multi-center thai university-based surgical intensive care unit study (THAI-SICU study): Incidence of acute myocardial infarction and associated factors - Waraporn Chau-In (2018)
© 2016, Medical Association of Thailand. All rights reserved. Introduction: To describe the incidence, characteristics and outcomes of acute myocardial infarction (AMI) and determine risk factor(s) of AMI in THAI-surgical intensive care unit (SICU). Material and Method: This study was multicenter prospective cohorts study that conducted data from 9 university-affiliated SICUs in Thailand between April 2011 and January 2013. We collected and evaluated data of AMI events. The patients were followed-up for up to 28 days after admitted to the SICUs. Results: The overall incidence of AMI in SICU was 1.4% (66 of 4,652 patients). Non-ST elevated MI was the most common electrocardiography (ECG) presentation (75%). The common clinical sign and symptom of AMI included ECG changes (53%) and elevation of cardiac enzymes (48.5%). Patients with AMI had significantly higher 28-day mortality rate (28.8% versus 13.6%, p<0.001) than those with non-MI. The Acute Physiologic and Chronic Health Evaluation (APACHE) II scores (RR 1.04, 95% CI 1.01-1.07, p = 0.003) and age >65 year (RR 2.54, 95% CI 1.36-4.75, p = 0.003) were significant risk factors of AMI. Conclusion: The incidence of AMI in the SICU was uncommon but led to significantly higher mortality rates. The APACHE II score and age >65 year were significant predictors of AMI in SICU.